THE INFLUENCE OF THE MARKETPLACE AND STORE ENVI- RONMENT ON PURCHASE DECISION OF MS GLOW SKINCARE PRODUCT AT SAMARINDA - Buana Raja, Muhammad Rezky (Magister Manajement Studies Program, 2025)
This study hides the influence of market and store environment on purchasing decisions on skin care products MS Glow Samarinda. The study used a quantitative approach, with data obtained using a structured questionnaire from 90 correspond-ents in an online survey conducted in Samarinda City, Indonesia. The results of this study will show that how the market and store environment have an influence on consumer purchasing decisions. The processing of this research data uses the Statistical Package for Social Science (SPSS) 29 program and shows the results that consumer perceptions of the marketplace and store environment can influence consumer behavior, with positive perceptions that lead to increased purchasing decisions.